About the scientific conference volume titled “The law enforcement scientific factors of criminal prosecution and crime prevention” (Academic Journal of Internal Affairs, 2020)
The mentioned scientific conference volume which is a real book in the classical typographic sense of the word. The appearance with the white, glossy soft cover adoring sciences and including 357 numbered pages confirm for the readers to have here many useful things to read.  On the cover grows apparent the label in border guards’ green, with the emblematic figure of border guards, the Turul bird holding a sword with the claws, is already indicative for the producers of the volume. Pécs, indicated as the place of publishing, was the centre of the suspended Boarder Guard till the end of 2007. Within the Hungarian Border Science Association founded In the time of system change was in the Section Border Police active from 1991 (later Section Border Guard) set up the professional group Pécs by eight  enthusiastic and science appreciating border guard officers in 2000. This guard, celebrating his 20th anniversary next year, organised its first conference in connection with the feast day of St. László one year after its foundation. The first scientific book was published in 2002 and this year’s volume has the number XXI.
Keywords: book review; crime prevention; law enforcement